Evaluation of BIRC6 Expression in Oral Squamous Cell Carcinoma, Epithelial Dysplasia, Lichen Planus with and without Dysplasia, and Hyperkeratosis - Fateme Eskandari; Alireza Razavian; Razieh Zare; Shayan Ejlali; Alireza Razmahang; Milad Zanjani; Seyedeh Sara Aghili; Mohammad Amin Mahdiyar; Hossein Mofidi; Kamyar Abbasi; Ashkan Badkoobeh; Nafiseh Shamloo; et al. (Diagnostics, 2023)
Background: BIRC6, regarded as the pivotal member of the inhibitor of the apoptosis (IAP) family, has been linked to the development of different types of cancer in humans. The objective of this study was to examine the expression of BIRC6 in various oral conditions, including OLP with dysplasia (OLPD), hyperkeratosis (HK), OLP, epithelial dysplasia (ED), and oral squamous cell carcinoma (OSCC), to investigate its potential involvement in the development of OSCC and the pathogenesis and malignant transformation of OLP, which is known as a precancerous condition. Methods: In this retrospective cross-sectional study, 99 cases, consisting of 19 cases of OSCC, 21 cases of ED, 23 cases of OLP, 20 cases of OLPD, and 16 cases of HK as the control group, were investigated regarding BIRC6 expression by immunohistochemical staining. After that, the immunohistochemical expression of BIRC6 in the epithelial compartment was analyzed. Statistical analysis was performed to investigate the relationship between the expression of BIRC6 and clinicopathological variables. The statistical analysis of the data involved the use of one-way ANOVA, post hoc Tukey, Kruskal–Wallis, Chi-square, Spearman’s correlation, and Mann–Whitney tests. The significance level was set at p < 0.05. Results: Positive BIRC6 staining was found in 91.7% of the subjects of OLP, 88.1% of HK, 86.1% of ED, 93% of OLPD, and 94.7% of OSCC. OSCC showed the highest BIRC6 expression (p = 0.00). The average total staining score was remarkably greater in OSCC and dysplastic lesions compared with HK (p = 0.00, p = 0.00). Conclusions: While the current study suggested that BIRC6 may play a role in the tumorigenesis of OSCC, its role in the malignant transformation of OLP has yet to be definitively established.